Perceived Attitude Of Malay Student In Kota Bharu Secondary Schools Towards The English Language - Mazita, Mokhtar (2002)

(untitled)
The objectives of this research is to identify the perceived attitude of Malay students in Kota Bharu secondary schools towards English language acquisition, to identify the significance of the relationships, if their exist, between the attitude and achievement and the four factors i.e gender difference, social economic status, parental influence and teacher factors. Questionnaire and interview are used to collect the data from the respondents. To evaluate the performance of the organization, secondary data from journal, annual reports, bulletin and web site are used as supporting materials. The SPSS application package, especially the frequency and Pearson correlation programs were used to analyze the collected data. An observation of the interview was also used. The results show significant relationships between perceived attitude, achievement and the four factors in this study. This research achieved its objectives in answering all the questions raised. Although it manages to show significant relationship, there is still room for further research into students' achievement in English. Further research need to be done to determine other variables that also contribute to the said achievement.